A relative efficiency measure based on stock market index data - Kristýna Ivanková (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This article introduces a new measure of stock market efficiency. The measure specifies how much a stock market index deviates from Brownian motion and is computed from frequency representations of isoquantile shapes estimated from lagged index returns. We describe the theory behind the approach, discuss parameter choices and apply the novel measure on chosen indices.
Keywords: C14; G14; 330; isoquantile; Efficient Market Hypothesis; stock market index; efficiency measure